If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2 + y)(3y + 7) = 0 Reorder the terms: (2 + y)(7 + 3y) = 0 Multiply (2 + y) * (7 + 3y) (2(7 + 3y) + y(7 + 3y)) = 0 ((7 * 2 + 3y * 2) + y(7 + 3y)) = 0 ((14 + 6y) + y(7 + 3y)) = 0 (14 + 6y + (7 * y + 3y * y)) = 0 (14 + 6y + (7y + 3y2)) = 0 Combine like terms: 6y + 7y = 13y (14 + 13y + 3y2) = 0 Solving 14 + 13y + 3y2 = 0 Solving for variable 'y'. Factor a trinomial. (7 + 3y)(2 + y) = 0Subproblem 1
Set the factor '(7 + 3y)' equal to zero and attempt to solve: Simplifying 7 + 3y = 0 Solving 7 + 3y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 3y = 0 + -7 3y = 0 + -7 Combine like terms: 0 + -7 = -7 3y = -7 Divide each side by '3'. y = -2.333333333 Simplifying y = -2.333333333Subproblem 2
Set the factor '(2 + y)' equal to zero and attempt to solve: Simplifying 2 + y = 0 Solving 2 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + y = 0 + -2 Combine like terms: 2 + -2 = 0 0 + y = 0 + -2 y = 0 + -2 Combine like terms: 0 + -2 = -2 y = -2 Simplifying y = -2Solution
y = {-2.333333333, -2}
| -3(-5x+2)= | | (8x+1)2+5=10 | | 3x^4+33x^3+90x^2=0 | | -5(4x-2)= | | a^(1/3)*a^(4/3) | | 4x-7x-13=-3x+7-13 | | (6x+2)(3x-5)=(9x-4)(2x+4) | | p^2p/p^-5 | | 2/3x-1=-1/3x-5 | | (2x^4+6y)(2x^4-6y)= | | 2(3x+3)=5(x-4) | | -3(x+5)=2-2x | | 12x^2+4x+15=0 | | 3(7r-12)=21r-6 | | 63+30t+3t^2=0 | | 4x+2.9=9.7 | | 7(x+1)=-2(x-4)+x | | 12k-3(2k-3)=45 | | -5y-15=7y+9 | | -5-15=7y+9 | | 2(1.6x)-1.33=-x+4.13 | | 4z+17=3z+4 | | 5-2x-4x=9 | | 27(2/3n) | | 500/3000 | | 7/3xb^4 | | y=-15-(-2)-(11-6) | | 2x^2y+4xy-58y=0 | | y=-20+30-40-(-50) | | (10-y)+y=3.09 | | y=x^3+2x^2-8x-5 | | (9+z)(5z+3)=0 |